تجانس الأسلوب المعرفي لدى أمهات التلاميذ وتأثيره على التحصيل الدراسي - ضو مريم; واكد رابح (University of Eloued جامعة الوادي, 2023)
يسلط هذا المقال الضوء على أهم المفاهيم المعرفية في علم النفس المعرفي والنظريات المعرفية، وهي الأساليب المعرفية، والتي لاقت اهتماما كبيرا في الأبحاث والدراسات التربوية، ومدى أهميتها في الجانب التربوي والتعليمي، لأنها تعتبر من طرق التفضيل في استقبال المعرفة. حيث يتناول هذا المقال اللأساليب المعرفية في إطار العلاج المعرفي السلوكي، وكيف يمكننا من خلالها مساعدة الأولياء الذين يشكون تدني التحصيل الدراسي لدى أبنائهم، ومساعدتنا كمهنيين في تذليل الصعوبات العلائقية من خلال إدراكنا للأساليب المعرفية للمتعلم وأهمية التجانس في البيئة التعليمية والتربوية، ومحاولة العمل على تجانس الأسلوب المعرفي للأمهات عبر جلسات العلاج المعرفي السلوكي، لتحسين المستوى التحصيلي، وذلك من خلال العمل الميداني مع وضعيات عيادية لأمهات تلاميذ ذوي تحصيل دراسي منخفض. Abstract: The current study aims to find out the impact of the harmonization of the cognitive styles of mothers and students on academic achievement from a cognitive-behavioral perspective in order to help parents who complain of low academic achievement in their children, as well as help specialists in overcoming relational difficulties, Through field work with clinical situations for the mothers of students with low academic achievement, and their number was two, who were deliberately chosen from among the clients of the psychiatric clinic, where the mothers underwent sessions of cognitive behavioral therapy, which works to correct misconceptions and distorted concepts, The data of the study was collected by applying the progressive matrices test of intelligence, the diagnostic uniform battery tests, and the psychological family drawing test, as well as the results of their academic achievement, in addition to the results of interviews and clinical sessions. After presenting and analyzing the results, the results were positive in terms of the nature of the relationship between the mother and the case, which led to the improvement of the students' academic results.
قراءة عيادية من منظور معرفي سلوكي
Keywords: الأساليب المعرفية; العلاج المعرفي السل; كي; التحصيل الدراسي; cognitive styles; cognitive behavioral therapy; School acquisition